Making CSA-CIS-One-health Innovations Inclusive: AICCRA Ghana activities on mainstreaming and customizing innovations to women and youth needs - Obeng, Faustina; Damba, Osman Tahidu; Yeboah, Stephen; Wilson, Michael; Martey, Francisca; Clottey, Victor; Nii-Koi, Gordon; Dalaa, Mustapha Alasan; Agboton, Cyriaque; Tepa-Yotto, Ghislain (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
AICCRA Ghana prioritized cowpea and sweet potato value chains for their women friendliness in addition to maize, yam and tomatoes which also involve substantial numbers of women and youth in their value chains. The project prioritized CSA technologies that are women and youth friendly including their lower associated drudgery, affordability, availability and socio-cultural acceptability. To disseminate these technologies, AICCRA Ghana ensured plots selected to host demonstration were convenient to women. The project intentionally selected women’s plots to host demonstration as a way to demystify cultural norms around the productivity of women’s farms. The project further customized field days to the meetings of women’s VSLA groups to encourage more women to attend. The project disseminated CIS through community radios which reached many women and was crucial for farm decision making especially the harvesting of cowpea. To improve women’s decision making in farmer based organizations, AICCRA Ghana convened women’s sub-groups and engaged in transformative dialogues around gender norms that impede their participation and leadership. This improved women’s collective action and improved their voice in FBOs.